2018
DOI: 10.3390/agriculture8050067
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supplemental Irrigation on Canopy Temperature Depression, Chlorophyll Content, and Water Use Efficiency in Three Wheat (Triticum aestivum L. and T. durum Desf.) Varieties Grown in Dry Regions of Jordan

Abstract: Abstract:One critical challenge facing the world is the need to satisfy the food requirements of the dramatically growing population. Drought stress is one of the main limiting factors in the wheat-producing regions; therefore, wheat yield stability is a major objective of wheat-breeding programs in Jordan, which experience fluctuating climatic conditions in the context of global climate change. In the current study, a two-year field experiment was conducted for exploring the effect of four different water reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…The superiority of growth traits, total chlorophyll and phenological development stages obtained herein at full irrigation regime (five irrigations) may be due to that the sufficient soil moisture in the root zone help the plants to absorb greater amount of water and nutrients which enhancing internodes elongation and cell division as well as improving pigments and photosynthetic process and metabolites accumulation and consequently increased growth periods. In this concern, many researchers reported that providing the wheat plants with sufficient moisture caused an increase in plant height (Razaq et al, 2016, Soomro et al, 2016, flag leaf area (El-Metwally et al, 2015), chlorophyll (Abdelraouf et al, 2013 andAl-Ghzawi et al, 2018) and days from sowing till heading and maturity Mekkei &El Haggan, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The superiority of growth traits, total chlorophyll and phenological development stages obtained herein at full irrigation regime (five irrigations) may be due to that the sufficient soil moisture in the root zone help the plants to absorb greater amount of water and nutrients which enhancing internodes elongation and cell division as well as improving pigments and photosynthetic process and metabolites accumulation and consequently increased growth periods. In this concern, many researchers reported that providing the wheat plants with sufficient moisture caused an increase in plant height (Razaq et al, 2016, Soomro et al, 2016, flag leaf area (El-Metwally et al, 2015), chlorophyll (Abdelraouf et al, 2013 andAl-Ghzawi et al, 2018) and days from sowing till heading and maturity Mekkei &El Haggan, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a great attention has been directed paid to increase the productivity of such important crop, therefore the strategies of agricultural policies have to be focused on minimizing the gap between the Egyptian production and consumption via increasing wheat production through using tolerant genotypes for biotic and abiotic stress circumstances and using the optimal agricultural practices taking into account the limited available water reserves on global scale (Loggini et al, 1999 andVarga et al, 2015). One of the major effects of climate changes particularly in arid and semi-arid regions will be increased frequency and severity of drought stress which is considered the most critical environmental stresses and one of the limiting factors in the wheat-producing regions (IPCC, 2013 andAl-Ghzawi et al, 2018). Water stress can result in a negative impact on phenological growth stages, reduced biomass production and grain yield (Kilic &Yagabsanlar, 2010 andSeleiman et al, 2011).…”
mentioning
confidence: 99%
“…The trend was similar in all cultivars, and the lowest WUE was found at the d 100 treatment. WUE was affected by the irrigation level and also by the cultivar, which is very important, as, in limited water supply, it is better to find cultivars tolerant to water stress that can efficiently use water [24,25,[45][46][47][48]. In addition, the WUE that was found was much higher than in other species such as maize, and this is because basil and also other aromatic and medicinal plants are not harvested for grains, but they are harvested at full anthesis and do not require water for their whole growth period [46][47][48].…”
Section: Water Use Efficiencymentioning
confidence: 99%
“…Possibly, the chlorophyll "b" is more resistant to degradation than chlorophyll "a" and can be an important index of hydric stress. However, contrarily to these results, in literature was observed decreasing in sugarcane (Gonçalves et al, 2017) and wheat (Al-Ghzawi et al, 2018) or not effect in Thymus daenensis (Bahreininejad et al, 2013) on chlorophyll "b" under soil hydric deficit.…”
Section: Discussionmentioning
confidence: 77%